El 'exilio' uruguayo en Argentina: Intersecciones entre memoria, ciudadanía y democracia. - Merenson, Silvina (European Review of Latin American & Caribbean Studies, 2015)
This article explores the interdependencies between 'memory', 'citizenship', and 'democracy' introduced by the Uruguayan 'exile' in Argentina together with the coalition Frente Amplio de Uruguay en Argentina (FAUA - Broad Front of Uruguay in Argentina). Starting from a critical review of Transnational Studies and ethnographic field work, this article analyses the political construction of the 'exile' and the historical process followed by the FAUA from 1982 up to the present. The article questions the ways in which memories work in regard to the recent past upon value judgements and possible conditions of'transnational citizenship'. Il maintains that the forms of processing notions of belonging to the political community of origin, as well as those acts of identification and political capital that provide the experience of'exile', offer a privileged point from which to reflect on the ways in which this activism explains the process of democratization in Uruguay.